In-depth LC-MS and in-vitro studies of a triterpenoid saponin capilliposide-A metabolism modulation in gut microbiota of mice - Zhao, Huan; Hu, Xueli; Guan, Shenghong; Cai, Jinhong; Li, Xiaohan; Fang, Jiaxi; Lin, Bo; Zhu, Wei; Tian, Jingkui; Jin, Juan; He, Qiang; Zhang, Xiaoyong (Frontiers in Pharmacology, 2024)
Introduction: Some herbal ingredients can reshape the composition of the gut microbiome as well as its metabolites. At the same time, the gut microbiota can also affect drug metabolism. A large number of studies have reported that saponins are biotransformed under the action of intestinal microorganisms to improve drug efficacy and bioavailability. Capilliposide A is a triterpenoid saponin, which is derived from Lysimachia capillipes Hemsl. CPS-A has anti-inflammatory pharmacological activity, but the substance basis in vivo is unknown at present, so studies on the interaction between intestinal microorganisms and CPS-A may clarify the pharmacodynamic substance basis of CPS-A. Methods: This study established a colitis mouse model, collected sterile feces from normal mice and colitis mice, and incubated CPS-A with two different intestinal flora in vitro. Based on LC-MS, the metabolic process of CPS-A mediated by intestinal microbes and the intervention effect of CPS-A on intestinal microbiome derived metabolites were studied. Results: The results of experiments indicate that intestinal microorganisms can mediate the biotransformation of CPS-A and metabolize it into corresponding deglycosylation products, thereby promoting its drug effect. Not only that, CPS-A can also promote metabolites such as Deoxycholic acid, Histamine, 3-Hydroxytridecanoic acid, and Indole-3-acetic acid in the intestinal microbiota of mice with colitis. This may result in anti-colitis effects. CPS-A mainly involved in metabolic pathways such as azathioprine and mercaptopurine, which may also have beneficial or adverse effects. Discussion: This study on the interaction between CPS-A and microbiota provides a new idea for the study of traditional Chinese medicine with poor oral bioavailability. The regulatory effect of CPS-A on the metabolites of intestinal flora in colitis mice was also found. It laid a foundation for exploring the mechanism of action of saponins on colitis mice.